2021
DOI: 10.1021/acschemneuro.1c00381
|View full text |Cite
|
Sign up to set email alerts
|

Securinine Promotes Neuronal Development and Exhibits Antidepressant-like Effects via mTOR Activation

Abstract: Impaired differentiation of newborn neurons or abnormalities at the synapses resulted from stress maladaptation could be the key etiology of depression. Recent studies have shown that mTOR, a crucial factor for neuronal differentiation and synapse development, acts as a common factor that mediates the rapid antidepression effects of several new-class antidepressants. In this study, the antidepressant-like activity of securinine, an alkaloid that has central nervous system stimulation ability, was investigated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…The depression‐like behavior was tested by a forced‐swim test as previously described (Xiao et al , 2021). Four mice were tested simultaneously in an opaque white compartment (66.7 cm long, 16 cm wide, and 26 cm high), which is equally divided into four parts, each containing a clear Plexiglas cylindrical container.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The depression‐like behavior was tested by a forced‐swim test as previously described (Xiao et al , 2021). Four mice were tested simultaneously in an opaque white compartment (66.7 cm long, 16 cm wide, and 26 cm high), which is equally divided into four parts, each containing a clear Plexiglas cylindrical container.…”
Section: Methodsmentioning
confidence: 99%
“…Experimenters were blind to the genotypes during testing. More behavioral experiments were performed following our previous protocols (Guo et al, 2021(Guo et al, , 2022Xiao et al, 2021;Yang et al, 2021c), and the detailed procedures are described as follows.…”
Section: Behavior Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18][19] Several studies have shown that the mTOR signalling pathway plays a crucial role in the formation of nerve synapses, neuronal survival, nerve cell development, and axonal regeneration and extension. [20][21][22] Identifying the underlying molecules associated with the mechanisms downstream of the mTOR pathway and neural regeneration may provide useful therapeutic targets for CNS injury. Studies have shown that CD44 is closely related to axonal development.…”
Section: Discussionmentioning
confidence: 99%